2015
DOI: 10.1038/srep15646
|View full text |Cite
|
Sign up to set email alerts
|

SKLB-677, an FLT3 and Wnt/β-catenin signaling inhibitor, displays potent activity in models of FLT3-driven AML

Abstract: FLT3 has been identified as a valid target for the treatment of acute myeloid leukemia (AML), and some FLT3 inhibitors have shown very good efficacy in treating AML in clinical trials. Nevertheless, recent studies indicated that relapse and drug resistance are still difficult to avoid, and leukemia stem cells (LSCs) are considered one of the most important contributors. Here, we report the characterization of SKLB-677, a new FLT3 inhibitor developed by us recently. SKLB-677 exhibits low nanomolar potency in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…While the median survival after the start of treatment in control treated mice are similar between these studies, the overall median survival from the MV4;11 injection are farther apart, with the original study reporting a median time of 35 days and this replication attempt reporting 59 days due to the added time from injection to beginning of treatment. Comparatively, other published studies using this model have reported a range of median survival times, such as 41 days (O'Farrell et al, 2003), 51 days (Dorn et al, 2009; Lopes de Menezes et al, 2005; Ma et al, 2015), and 60 days (Hardwicke et al, 2009) after intravenous injection of MV4;11 cells into NOD-SCID mice. To summarize, for this experiment we found the survival results were not in the same direction as the original study and not statistically significant where predicted.
10.7554/eLife.25306.008Figure 4.Efficacy study of I-BET151 in xenograft mouse model of MLL-fusion leukaemia.Female NOD-SCID mice were xenotransplanted with 1 × 10 7 MV4;11 cells after conditioning with Busulfan.
…”
Section: Resultsmentioning
confidence: 88%
“…While the median survival after the start of treatment in control treated mice are similar between these studies, the overall median survival from the MV4;11 injection are farther apart, with the original study reporting a median time of 35 days and this replication attempt reporting 59 days due to the added time from injection to beginning of treatment. Comparatively, other published studies using this model have reported a range of median survival times, such as 41 days (O'Farrell et al, 2003), 51 days (Dorn et al, 2009; Lopes de Menezes et al, 2005; Ma et al, 2015), and 60 days (Hardwicke et al, 2009) after intravenous injection of MV4;11 cells into NOD-SCID mice. To summarize, for this experiment we found the survival results were not in the same direction as the original study and not statistically significant where predicted.
10.7554/eLife.25306.008Figure 4.Efficacy study of I-BET151 in xenograft mouse model of MLL-fusion leukaemia.Female NOD-SCID mice were xenotransplanted with 1 × 10 7 MV4;11 cells after conditioning with Busulfan.
…”
Section: Resultsmentioning
confidence: 88%
“…Cell proliferation assays were carried out as previously reported. 36 A variety of human pancreatic cancer cell lines were seeded at an appropriate density in 96-well plates (1000-5000 cells per well) overnight. Then they were treated with indicated concentrations of LY-1816 or other agents.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…8 Aberrant Wnt/β-catenin pathway activity has been demonstrated to be essential for AML initiation and progression and is required for LSC selfrenewal and survival. 9,10 Recent preclinical studies indicate that inhibiting the Wnt pathway is promising for AML treatment, 6,11 which implies that targeting the Wnt pathway may also eliminate the LSC population in AML.…”
Section: Introductionmentioning
confidence: 99%